Exploiting Idioms and Proverbs of Vietnamese Regions in Teaching Mathematics in Primary Schools - Cong-Kien Hoang; Dieu-Thuy Thi Pham; Tung Do; Tinh Thi Pham; Minh-Nguyet Thi Nguyen; Quoc-Chung Vu; Duy-Cuong Le; Thuy-Chung Nguyen (Emerging Science Journal, 2022)
Mathematics and idioms, as well as proverbs, all reflect the laws of life. At the same time, primary school children may have heard idioms and proverbs before attending school. Therefore, there are many possibilities to exploit and apply idioms and proverbs in teaching mathematics in primary schools. This study aims to identify appropriate situations and apply idioms and proverbs in different regions of Vietnam to teaching mathematics. The researchers selected 1155 expressions related to mathematics from many typical pieces of research on idioms and proverbs in Vietnam. After surveying 1822 teachers three times in many provinces and cities in all 3 regions of Vietnam: the North, the Central and the South, the researchers have classified the data according to the criteria from closed to open-ended questions. The results show a prominent level of interest (level 4/5) of all teachers participating in the survey, and there is no difference in the effectiveness in the three regions, but there is a clear difference in regions in using idioms and proverbs. Particularly, identifying situations to teach geometric and quantitative knowledge, as well as probability and statistics, allows one to apply idioms and proverbs at a high level. It is concluded that if idioms and proverbs from Vietnamese regions are appropriately selected and applied in teaching mathematics in primary schools, they will contribute to improving students' mathematical ability and preserving the national cultural heritage. Doi: 10.28991/ESJ-2022-SIED-015 Full Text: PDF